2013
DOI: 10.3390/md11093472
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Evaluation of Thiazinoquinones as Anti-Protozoal Agents

Abstract: Pure compound screening has identified the dioxothiazino-quinoline-quinone ascidian metabolite ascidiathiazone A (2) to be a moderate growth inhibitor of Trypanosoma brucei rhodesiense (IC50 3.1 μM) and Plasmodium falciparum (K1 dual drug resistant strain) (IC50 3.3 μM) while exhibiting low levels of cytotoxicity (L6, IC50 167 μM). A series of C-7 amide and Δ2(3) analogues were prepared that explored the influence of lipophilicity and oxidation state on observed anti-protozoal activity and selectivity. Little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Ascidiathiazone A ( 109 ) (Figure ) was a moderately potent in vitro growth inhibitor of P. falciparum K1 strain (IC 50 = 3.3 μM) and Trypanosoma brucei rhodesiense (IC 50 = 3.1 μM). However, it was effectively inactive toward T. cruzi and Leishmania donovani and exhibited low cytotoxicity against a mammalian cell line (L6, IC 50 = 167 μM) …”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…Ascidiathiazone A ( 109 ) (Figure ) was a moderately potent in vitro growth inhibitor of P. falciparum K1 strain (IC 50 = 3.3 μM) and Trypanosoma brucei rhodesiense (IC 50 = 3.1 μM). However, it was effectively inactive toward T. cruzi and Leishmania donovani and exhibited low cytotoxicity against a mammalian cell line (L6, IC 50 = 167 μM) …”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…Mani and colleagues reported antiplasmodial activity in the bromotyrosine derivative araplysillin I ( 62 ) from the South Pacific Solomon Islands sponge Suberea ianthelliformis [71]. Lam and colleagues extended the pharmacology of the New Zealand ascidian dioxothiazino-quinoline-quinone metabolite ascidiathiazone A ( 63 ) by demonstrating it to be a moderate growth inhibitor of chloroquine and a pyrimethamine resistant P. falciparum K1 strain, and noting that changing the quinolone-based structure to incorporate benzofuran or benzothiophene moieties yielded particularly potent antimalarials [72]. Farokhi and colleagues characterized new glycosphingolipids axidjiferoside A–C ( 64 – 66 ) from the Senegal marine sponge Axinyssa djiferi with potent antimalarial activity against chloroquine-resistant FcB1/Colombia P. falciparum strain [73].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Lam and colleagues reported that the known dioxothiazino-quinoline-quinone metabolite ascidiathiazone A ( 63 ), isolated from a New Zealand ascidian, moderately inhibited the growth of T. brucei rhodesiense , but was ineffective against T. cruzi and L. donovani [72]. Balunas and colleagues isolated the polyketide coibacin A ( 83 ) from a Panamanian marine cyanobacterium Oscillatoria sp., and observed potent activity against L. donovani axenic amastigotes [88].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…such as Schistosoma and Leishmania, classified as neglected tropical diseases (NTDs) due to the absence of efficient and consistent politics based on prevention and a consequent lack of investments by pharmaceutical industries [3]. In the frame of our studies aiming to explore new chemical entities that can be employed for the discovery of new drugs against malaria and other parasitic diseases [4][5][6][7][8][9], we have recently identified the bicyclic 1,1-dioxo-1,4-thiazine system fused to the quinone ring as a new scaffold active against P. falciparum and Schistosoma mansoni [4][5][6][7][8][9] exploiting natural marine metabolites as model compounds [10][11][12][13][14]. This work, based on the model of natural marine metabolites, aplidinone A and B (1 and 2), has yielded a chemical library of synthetic thiazinoquinones (3-22, Figure 1), which was funneled into a large screening for the search of antimalarial agents [4,6,9].…”
Section: Introductionmentioning
confidence: 99%